Automatic Car Control Prototype With Sound Application In Android Arduino Uno-Based: Automatic Car Control Prototype With Sound Application In Android Arduino Uno-Based - Muhammad Ade Dharamawan Nasution; Dedy Hartama; Fitri Anggraini; Rafiqa Dewi; Eva Desiana (Institute of Computer Science (IOCS), 2020)
A car control device has been made with a voice application on an Android smartphone based on Arduino UNO. This tool uses HC-05 as a Bluetooth transmission media, Arduino Uno as the main controller and 2 DC motors as output. App Inventor is used to make a sound application on a smartphone, if the application receives a